Queer Ecologies : Sex, Nature, Politics, Desire. - Mortimer-Sandilands, Catriona; Erickson, Bruce (Bloomington : Indiana University Press, 2010)
As a whole, Queer Ecologies stands as a powerful corrective to views that equate "natural" with "straight" while "queer" is held to be against nature.
Cover -- Title -- Copyright -- Contents -- Acknowledgments -- Introduction: A Genealogy of Queer Ecologies -- Part 1: Against Nature? Queer Sex, Queer Animality -- 1 Eluding Capture: The Science, Culture, and Pleasure of "Queer" Animals -- 2 Enemy of the Species -- 3 Penguin Family Values: The Nature of Planetary Environmental Reproductive Justice -- 4 Queernaturecultures -- Part 2: Green, Pink, and Public: Queering Environmental Politics -- 5 Non-white Reproduction and Same-Sex Eroticism: Queer Acts against Nature -- 6 From Jook Joints to Sisterspace: The Role of Nature in Lesbian Alternative Environments in the United States -- 7 Polluted Politics? Confronting Toxic Discourse, Sex Panic, and Eco-Normativity -- 8 Undoing Nature: Coalition Building as Queer Environmentalism -- 9 Fragments, Edges, and Matrices: Retheorizing the Formation of a So-called Gay Ghetto through Queering Landscape Ecology -- Part 3: Desiring Nature? Queer Attachments -- 10 "The Place, Promised, That Has Not Yet Been": The Nature of Dislocation and Desire in Adrienne Rich's Your Native Land/Your Life and Minnie Bruce Pratt's Crime Aganist Nature -- 11 "fucking close to water": Queering the Production of the Nation -- 12 Melancholy Natures, Queer Ecologies -- 13 Biophilia, Creative Involution, and the Ecological Future of Queer Desire -- List of Contributors -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Human ecology; Electronic books